Quality of Distance Learning in Kirovohrad Region, Ukraine, During Quarantine Restrictions - Voloshyna, Olga (Educational Challenges, 2021)
The issue of distance learning became relevant in early spring 2020 due to quarantine measures caused by the pandemic. The issue of transition to distance learning for all levels of education has become acute and lightning fast. In the conditions of globalization of the modern world, when information and timeliness of its receipt play a decisive role in competitive advantage, the content of education changes dramatically. The competitiveness of human capital is directly correlated with the requirements of the new information society, in which the knowledge aging is significantly reduced, and new opportunities for their acquisition will appear. A promising and extremely relevant area of modern higher education development under quarantine, as well as integration into European and world education is the active introduction of distance learning technologies in the educational process. The article analyzes the monitoring study of the general secondary educational institutions of Kirovograd region students’ parents attitude to distance learning. The purpose of the study is to determine the level of distance learning quality during quarantine restrictions. Research methods include general scientific methodology of research and principles of a systematic approach; case study methods. The results of the study are considered and the current state of quality assurance of general secondary education has been analyzed. The data obtained during the monitoring should be considered as an information basis for effective management of the educational process, to improve its content, methodological and organizational aspects. Conclusions. The most important elements of distance learning should be: the creation of practical situations during the educational process, the opportunity for students to express themselves constantly, self-realization, educational process clarity, its individualization, technical and technological support of distance education. Successful solution of the problem of effective implementation and harmonious development of distance education in Ukraine will increase the quality level, higher education accessibility, integration of the national education system into scientific, research and production, social and cultural information infrastructure of the European / world community.